ANTI-CRISIS FINANCIAL MANAGEMENT AS THE BASIS OF FINANCIAL MANAGEMENT OF DOMESTIC ENTERPRISES - NIKOLCHUK, J.; LOPATOVSKA, O. (Herald of Khmelnytskyi National University. Economic sciences, 2021)
This article offers a rationale for the need for crisis financial management in today’s business environment, analyzes the basic interpretation of the concept of "crisis financial management" and establishes that crisis financial management is a component of crisis management. We believe that anti-crisis financial management is a mechanism of financial influence, a set of measures at the stages of identifying crisis factors, effective diagnosis, prevention and neutralization of the crisis based on a system of specific methods, principles and techniques of financial management. The structure of the mechanism of anti-crisis financial management of the enterprise is made, which includes: goals, tasks, objects, sub-measures, functions, principles and methods of anti-crisis management. The reasons of necessity of anti-crisis management at the enterprises are substantiated and the mechanism of anti-crisis financial management at the enterprises is formulated. It is argued that the use of crisis management includes a set of actions of both strategic and tactical nature, based on what are called types of crisis management and their stylistic characteristics. As a result of consolidation of approaches to defining the essence and foundations of crisis financial management, it was found that in the modern world economy the problems of understanding anti-crisis financial management are extremely relevant. In this regard, anti-crisis financial management is based on a careful analysis of the financial and economic condition of the company and the development of anti-crisis measures that will allow the company to prevent and avoid bankruptcy, as well as increase the efficiency of its activities. Based on the study, we can definitively define the concept of "crisis financial management of the enterprise" as a set of constantly organized management, which is based on the use of specific methods, principles and techniques of financial management of the enterprise, including components aimed at preventing and neutralizing the financial crisis. financial potential of the enterprise. Anti-crisis financial management can be successful if it is timely and, very importantly, preventive. Thus, only such management in today’s rapidly changing conditions is able to achieve the goal and effectively solve the problems of the overall management system of the enterprise.